Hubungan Pola Makan dan Citra Tubuh dengan Status Gizi pada Remaja Sekolah Menengah Atas di Kota Padang: Eating Patterns and Body Image in Relation to Nutritional Status among Adolescents in Padang City High Schools - Elda, Frima; Novirsa, Randy; Kasra, Kamal; Azmi, Fadilla; Delviana, Adelia; Surya, Rezi Fatrima (Universitas Airlangga, 2026)
Introduction: In Indonesia, especially in urban areas, lifestyle and environmental changes contribute to a triple burden of nutritional problems among adolescents, where undernutrition (9.8%) coexists with increasing cases of overweight and obesity (8.6%). This condition reflects a growing imbalance between adolescents’ eating patterns and body perception. Objective: This study aimed to explore the relationship between body image and eating patterns among adolescents with normal, overweight, and obese nutritional status. Methods: A cross-sectional study was applied in this study and data were analyzed using the Chi-square test by comparing observed and expected frequencies. The data collected included the nutritional status as the dependent variable, body image, socioeconomic factors, and eating patterns as independent variables. The study was conducted in two selected public high schools in Padang City, involving 1,299 population students aged 15–18 years, with a total sample of 377 respondents were selected. Data collection was conducted from August 2024 to March 2025. Results: Results showed that 33.7% of students experienced either undernutrition or overnutrition, 64.5% had poor eating behaviors, and 42.2% reported a negative body image. There were significant associations between eating patterns (p-value=0.049; POR=1.63) and body image (p-value=0.001; POR=29.2) with nutritional status among high school students in Padang City. Conclusion: Understanding the relationship between eating patterns, body image, and nutritional status is essential for developing effective school-based interventions and health promotion strategies.